Irrigating Solutions in Endodontics: evidence and deficiencies (Research, Society and Development, 2023)
The aim of this study was to review the literature regarding irrigating solutions used in endodontic procedures, highlighting the most used ones and highlighting new alternatives for irrigating agents. The methodology was intended to perform an integrative literary review that was developed in six phases, namely: a) development of the research question; b) definition of descriptor terms and search platforms, c) definition of eligibility criteria used; d) careful analysis of the included studies; e) definition of the information to be extracted from the articles taken from the databases; f) interpretation of the results and presentation of the synthesis of knowledge, in which the guiding question was elaborated through the PICo strategy. Thus, bibliographical searches were carried out in the electronic portals PubMed, BVS and Ebsco using the keywords: Endodontics; Chlorhexidine and Sodium Hypochlorite, in which 22 articles were chosen for the development of this work. Sodium hypochlorite (NaOCl), ethylenediaminetetraacetic acid (EDTA) and chlorhexidine (CHX) are the most effective and safe irrigating solutions, with NaOCl and CHX being the most popular ones used. Thus, it is clear how important is the applicability of irrigating solutions during endodontic therapy. Because, through its administration, there is a positive response in the control of microbial agents that are found in the root canal. The sterilization of the root canal system is not possible and the available substances and techniques still have deficient points, due to this new irrigating solutions have been studied to add to endodontic interventions.